Prostatic malakoplakia: a case report with review of the literature. Issue 3 (27th March 2018) - Ho, Matthew; Wu, Jeremy; Skinnider, Brian; Kavanagh, Alex
Abstract: Prostatic malakoplakia is a rare benign tumor with few reported cases in the literature. A 61-year-old male with a history of Escherichia coli urinary tract infection (UTI) and gross hematuria presented for evaluation with prostate-specific antigen (PSA) level of 16.0 ng/mL and a 1.5 cm palpable prostatic nodule highly suggestive of prostate cancer. Cystoscopy was unremarkable. Transrectal ultrasound-guided biopsy was performed. Pathologic analysis demonstrated prostatic malakoplakia without evidence of associated malignancy. The patient remains on surveillance with regular physical examination and PSA serum testing. Prostatic malakoplakia is a rare diagnosis with clinical examination findings highly suggestive of prostate cancer and without known associated malignancy risk.